Greenhouse climate control system based on fuzzy logic - L. A. Payuk; N. A. Voronina; A. D. Umurzakova; E. E. Lazutkina; K. V. Khatsevskiy (Омский научный вестник)
Paper is devoted to development and research of the fifth generation greenhouse climate automatic control system. This system is based on fuzzy logic toolbox and it allows to automate control processes using the latest developments in this field. In the work the concept of «microclimate of greenhouse complex» for the region of the risky agricultural zone when growing large strawberries in a closed ground.